2022
DOI: 10.1007/978-3-031-08518-5_11
|View full text |Cite
|
Sign up to set email alerts
|

A Primer to Latent Profile and Latent Class Analysis

Abstract: This chapter gives an applied introduction to latent profile and latent class analysis (LPA/LCA). LPA/LCA are model-based methods for clustering individuals in unobserved groups. Their primary goals are probing whether and, if so, how many latent classes can be identified in the data, and to estimate the proportional size and response profiles of these classes in the population. Moreover, latent class membership can serve as predictor or outcome for external variables. Substantively, LPA/LCA adopt a person-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Nonetheless, small profiles (< 5%) are considered useful when the number of small classes is low (we have only one small class) and when the small class is interpretable and distinguished from other classes (P6 emerged early in the iterative process indicating that it is distinguished from other classes and we were able to interpret these values as being higher than all other profiles). 65 Moreover, a previous study also identified a group (25% of families) of high to very high…”
Section: Discussionmentioning
confidence: 92%
“…Nonetheless, small profiles (< 5%) are considered useful when the number of small classes is low (we have only one small class) and when the small class is interpretable and distinguished from other classes (P6 emerged early in the iterative process indicating that it is distinguished from other classes and we were able to interpret these values as being higher than all other profiles). 65 Moreover, a previous study also identified a group (25% of families) of high to very high…”
Section: Discussionmentioning
confidence: 92%
“…We employed latent profile analysis (LPA) to assess the complex relationship between drug type and drug-related behaviours, given that, as a latent variable mixture modelling approach, LPA is well-equipped to capture the complexities associated with polysubstance use that may be imperceptible when analysing individual factors alone [26]. Furthermore, LPA is similar to latent class analysis (LCA) in that they both use mixture modelling to identify hidden groups based on observed data, although importantly, LPA identifies different groups based on groupspecific means, while LCA identifies groups defined by the item's category-specific endorsement probability [27]. Although we considered both approaches, we opted for LPA over LCA given that we employed 5-and 7-level ordered categorical variables, which cannot be effectively leveraged by LCA as a result of its limitation in effectively accounting for ordinal data [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, though excluding participants without sufficient exposure to the treatment is reasonable, time criteria are always somewhat arbitrary. Latent class analysis of time on task might provide a more principled approach for this purpose (Bauer, 2022). Finally, the reliabilities of the source preference scales proved quite low in Study 2, as compared with Study 1 and Thomm et al (2021a).…”
Section: Limitationsmentioning
confidence: 95%